ANALISIS PENGGUNAAN MEDIA PROMOSI KESEHATAN LAYANAN (PITC) PROVIDER INITIATED TESTING COUNSELING PADA IBU HAMIL - Nurmiah Dongoran; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
The number of HIV/AIDS cases in Indonesia is still increasing, the national figure until January 2019 was recorded at 326,281 cases. HIV/Aids cases in Medan City are increasing. From 2006 to 2022 there were 8,385 cases recorded. This research is an explanatory research. The approach used in this research is a quantitative approach. This study uses a correlation analytic design with a cross sectional approach. Information about PITC services is necessary because most of the pregnant women in this study had never received information about PITC services (66.7%), where the majority of respondents were multigravida, so they had not received experience or knowledge about PITC in previous pregnancies.